O mural de Eduardo Kobra em Santa Maria: uma relação com a arte pública - Uberti, Mariete Taschetto (2014)
This research deals with the Public Art in Santa Maria / RS, with the main object of study Eduardo Kobra‟s mural accomplished in the Municipal Library of that city. The authors that help me to articulate and combine with the Public Art are Arend (2010); Alves (2011), Peixoto (2009, 2012) and Silva (2005), for the artist's contextualization in interaction with his work and the public, and theirs among themselves, considering the policies of articulation among artist, space, work, public and promoters of art. The urban public of the city of Santa Maria is analyzed on the view of works installation in these areas, and the influence of the Course of Arts and Letters of the Federal Uni-versity of Santa Maria, since 1964, having as basis the works of Foletto (2008) and Foletto and Bisoning (2001). Taking as its central point the artist Eduardo Kobra‟s work, his research and involvement with Public Art, I contextualize about the influ-ences that reverberate in his artistic production, articulating his productions with other artists who had / have connection with his research, and influence of graffiti and hip hop in his career. The photograph and the memory are treated as proposers of pos-sibilities and reflections on the current context and in the art, based on Bergson (2011), Catroga (2009) and Richoeur (2007). Considering the different looks, from interviews with groups of local artists and a representative of the government, the main instigator and deliberator of the art in the city, you can see the relevance of Kobra‟s work in the city to contemplate on the art scene on the conflict between the visual arts and the performance of the government. That has conditioned positions and oppositions in relation to the field of art and art in the city, where the public as an extra in the artistic field of Public Art in the city.